Linkage mapping and association analysis to identify a reliable QTL for stigma exsertion rate in rice - Liu, Yi; Fu, Dong; Kong, Deyan; Ma, Xiaosong; Zhang, Anning; Wang, Feiming; Wang, Lei; Xia, Hui; Liu, Guolan; Yu, Xinqiao; Luo, Lijun (Frontiers in Plant Science, 2022)
The commercialization of hybrid rice has greatly contributed to the increase in rice yield, with the improvement of its seed production capacity having played an important role. The stigma exsertion rate (SER) is a key factor for improving the outcrossing of the sterile line and the hybrid rice seed production. We used the Zhenshan 97B × IRAT109 recombinant inbred population comprising 163 lines and a natural population of 138 accessions to decipher the genetic foundation of SER over 2 years in three environments. Additionally, we detected eight QTLs for SER on chromosomes 1, 2, and 8 via linkage mapping. We also identified seven and 19 significant associations for SER using genome-wide association study in 2016 and 2017, respectively. Interestingly, we located two lead SNPs (sf0803343504 and sf083344610) on chromosome 8 in the qTSE8 QTL region that were significantly associated with total SER. After transcriptomic analysis, quantitative real-time PCR, and haplotype analysis, we found 13 genes within this reliable region as important candidate genes. Our study results will be beneficial to molecular marker-assisted selection of rice lines with high outcrossing rate, thereby improving the efficiency of hybrid seed production.